2023
DOI: 10.3389/fcimb.2023.1184245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quality/quantity mNGS and usual mNGS for pathogen detection in suspected pulmonary infections

Zhan Zhao,
Xuefen Chen,
Yubao Wang
et al.

Abstract: Improved metagenomic next-generation sequencing (mNGS), for example, quality/quantity mNGS (QmNGS), is being used in the diagnosis of pulmonary pathogens. There are differences between QmNGS and the usual mNGS (UmNGS), but reports that compare their detection performances are rare. In this prospective study of patients enrolled between December 2021 and March 2022, the bronchoalveolar lavage fluid of thirty-six patients with suspected pulmonary infection was assessed using UmNGS and QmNGS. The sensitivity of Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, a recent study on different clinical sample types, using dPCR, next generation sequencing (NGS) and conventional commercial qPCR simultaneously, showed that the most sensitive method was dPCR (99%), over NGS (86%) and conventional qPCR (64%) [38].…”
Section: Bacteriology Applicationsmentioning
confidence: 99%
“…However, a recent study on different clinical sample types, using dPCR, next generation sequencing (NGS) and conventional commercial qPCR simultaneously, showed that the most sensitive method was dPCR (99%), over NGS (86%) and conventional qPCR (64%) [38].…”
Section: Bacteriology Applicationsmentioning
confidence: 99%